The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1039/f29736901669
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite exchangers. Thermodynamic treatment when not all ions are exchangeable

Abstract: Zeolites normally provide a number of distinct intracrystalline environments for cations. These cations then have different exchange properties for each such environment. The standard free energy, enthalpy, entropy and equilibrium constant for exchange in the whole crystal have been related to those of cations in the several environments. Three possible limiting cases of partial ion exchange can be visualised : (1) a pseudo-equilibrium is rapidly attained but a further slow exchange takes place over still long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

1973
1973
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…The maximum level of exchange reaches 100 % only for univalent cations, so that the equivalent ionic fractions should be normalized by dividing them through the maximum exchange attainable for the multivalent ion. (Valverde et al 2001;Carmona et al 2008;Barrer and Klinowski 1972;Sherry 1968;Barrer et al 1973;Vansant and Uytterhoeven 1971) Singare et al (2008aSingare et al ( , 2008bLokhande et al 2007;Lokhande et al 2009) have investigated the ion exchange of univalent ions, both anions and cations, on resins, at very low concentrations and they have obtained values of the equilibrium constant at different total concentrations, in remarkable agreement, even without using corrections for the non-ideal behavior of the external solution and of the zeolite phase.…”
Section: Introductionmentioning
confidence: 84%
“…The maximum level of exchange reaches 100 % only for univalent cations, so that the equivalent ionic fractions should be normalized by dividing them through the maximum exchange attainable for the multivalent ion. (Valverde et al 2001;Carmona et al 2008;Barrer and Klinowski 1972;Sherry 1968;Barrer et al 1973;Vansant and Uytterhoeven 1971) Singare et al (2008aSingare et al ( , 2008bLokhande et al 2007;Lokhande et al 2009) have investigated the ion exchange of univalent ions, both anions and cations, on resins, at very low concentrations and they have obtained values of the equilibrium constant at different total concentrations, in remarkable agreement, even without using corrections for the non-ideal behavior of the external solution and of the zeolite phase.…”
Section: Introductionmentioning
confidence: 84%
“…The treatment of the effect of water activity on ion exchange selectivity was further expanded by Laudelout and coworkers (Laudelout and Thomas, 1965;Laudelout et al, 1971;. In more recent times, the ion exchange formalism has been extended to cation exchangers possessed of multiple sites and also to cation exchangers which exhibit incomplewG exchange (B-rrer and Klinowski, 1978;Barrer et al, 1973).…”
Section: Zeolite Datamentioning
confidence: 99%
“…In clays, pH-dependent site heterogeneity is a well known phenomenon (Peigneur et al 1975;Goulding & Talibudeen 1980; and this was used to explain the failure of the sub-regular model to describe adequately the Ba-NH4 exchange in montmorillonite (Elprince et al 1980). In zeolites, site heterogeneity can be very marked, giving rise to partial exchange (Barrer et al 1973; Barrer & Klinowski 1977) and also to phenomena in which some ions are irreversibly 'locked' into certain sites within the framework Lai & Rees 1976 a ,b).This heterogeneity arises from the existence of ' crystallograph distinct cation sites intimately mixed throughout an anionic framework ' (Barrer & Klinowski 1979a).…”
Section: (A) Introductionmentioning
confidence: 99%
“…A general statistical thermodynamic theory of isomorphous replacement in zeolites has also been given (Barrer & Klinowski 1977) and the subject has been considered also from the viewpoint of order-disorder theory (Barrer & Klinowski 1979 b).The first detailed report of a ternary ion exchange system in a zeol was by Barrer & Townsend (1978), and subsequently, detailed studies on the N a-C a-M g-A system have appeared Barri & Rees 1980). Other binary exchange studies (Barrer & Townsend 1976;Fletcher & Townsend 1980) have shown that the activity coefficients for ions in association with their equivalents of zeolite framework can vary in a complicated manner with exchanger composition, and considerations of other work (Barrer al. 1973;Barrer & Klinowski 1977) led to the conclusion that these variations must be ascribed to changing populations and compositions within the exchanger site sets that comprise the zeolite (Fletcher & Townsend 1980).…”
mentioning
confidence: 99%
See 1 more Smart Citation